Transcatheter coil embolisation of a pulmonary arteriovenous malformation in a neonate. Issue 4 (April 1994) - Grady, R. M.; Sharkey, A. M.; Bridges, N. D.
Abstract : Pulmonary arteriovenous malformations (PAVM) are a rare cause of cyanosis in neonates. A large PAVM in a neonate was successfully occluded by transcatheter embolisation. At six months follow up the PAVM was undetectable and no new lesions were found. Transcatheter embolisation should be considered as the primary treatment for a PAVM in a child of any age.